Slaughter characteristics of the export Sudan Desert Sheep - Babiker, S.A.; Abdel Hamid A.; Silverside, David E. (1988)
The Hammari sheep, as an ecotype of the export type Sudan desert sheep, was found to have an average liveweight of 62 kg, yielding 30 kg carcass and dressing percentage of 56.4. Data pertaining to mean, standard deviation, range and coefficient of variation for external body measurements, carcass measurements, carcass composition and components were given. Simple correlation coefficients between slaughter weight and live animal measurements and between carcass weight and carcass measurements were also shown.